Doktrin Poros Maritim Dunia Era Jokowi dan Keamanan di Bidang Maritim Studi Kasus: Perdagangan Narkotika Jalur Laut Tahun 2014-2018 - Nur Hakiki; Tri Cahyo Utomo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Immediately after being elected in 2014, President Joko Widodo put forward the desire to makeIndonesia's sea territory the main policy focus. This is implemented by issuing the doctrine ofthe